Student experiences across multiple flipped courses in a single curriculum. Issue 10 (18th September 2015) - Khanova, Julia; Roth, Mary T; Rodgers, Jo Ellen; McLaughlin, Jacqueline E
<x xml:space="preserve">Abstract</x> Context The flipped classroom approach has garnered significant attention in health professions education, which has resulted in calls for curriculum‐wide implementations of the model. However, research to support the development of evidence‐based guidelines for large‐scale flipped classroom implementations is lacking. Objectives This study was designed to examine how students experience the flipped classroom model of learning in multiple courses within a single curriculum, as well as to identify specific elements of flipped learning that students perceive as beneficial or challenging. Methods A qualitative analysis of students' comments (n = 6010) from mid‐course and end‐of‐course evaluations of 10 flipped courses (in 2012–2014) was conducted. Common and recurring themes were identified through systematic iterative coding and sorting using the constant comparison method. Multiple coders, agreement through consensus and member checking were utilised to ensure the trustworthiness of findings. Results Several themes emerged from the analysis: (i) the perceived advantages of flipped learning coupled with concerns about implementation; (ii) the benefits of pre‐class learning and factors that negatively affect these benefits, such as quality and quantity of learning materials, as well as overall increase in workload, especially in the context of multiple concurrent flipped courses; (iii) the role of the instructor in the flipped learning environment, particularly in engaging students in active learning and ensuring instructional alignment, and (iv) the need for assessments that emphasise the application of knowledge and critical thinking skills. Conclusions Analysis of data from 10 flipped courses provided insight into common patterns of student learning experiences specific to the flipped learning model within a single curriculum. The study points to the challenges associated with scaling the implementation of the flipped classroom across multiple courses. Several core elements critical to the effective design and implementation of the flipped classroom model are identified.